2021
DOI: 10.1155/2021/6681577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prosopis velutina Invasion on Soil Characteristics along the Riverine System of the Molopo River in North-West Province, South Africa

Abstract: Invasive alien plants are one of the major threats to ecosystems. Many invasive plant species, such as Prosopis species, have been introduced around the world and can alter the soil properties of invaded ecosystems. It is one of the most aggressive invasive plant invaders in the North-West Province of South Africa, but little information is available about their influence on soil properties. This study was conducted to investigate the effect of Prosopis velutina invasion on selected soil properties at five dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Similar C. spectabilis results reported for -infested soils in Australia L. camara where the higher soil pH was found in Lantana invaded sites compared to noninvaded sites (Osunkoya and Perrett 2011). In contrasting to the present study Comole et al (2021) reported that almost all soils collected from under the Prosopis velutina canopies had a significantly higher soil exchangeable Ca, K, Mg, and Na, organic matter (OM), total nitrogen (TN), available phosphorus (P), Electrical conductivity (EC), and cation exchange capacity (CEC) than the other sample positions, except for the pH which had the high value in inter-canopies. Electric conductivity: The electric conductivity did not vary significantly between infestation levels in D B Kuppe range.…”
Section: Cell Constantcontrasting
confidence: 99%
“…Similar C. spectabilis results reported for -infested soils in Australia L. camara where the higher soil pH was found in Lantana invaded sites compared to noninvaded sites (Osunkoya and Perrett 2011). In contrasting to the present study Comole et al (2021) reported that almost all soils collected from under the Prosopis velutina canopies had a significantly higher soil exchangeable Ca, K, Mg, and Na, organic matter (OM), total nitrogen (TN), available phosphorus (P), Electrical conductivity (EC), and cation exchange capacity (CEC) than the other sample positions, except for the pH which had the high value in inter-canopies. Electric conductivity: The electric conductivity did not vary significantly between infestation levels in D B Kuppe range.…”
Section: Cell Constantcontrasting
confidence: 99%
“…Although P. velutina reduced their abundances significantly, they were more associated with P. velutina than the other woody plant species. According to Comole et al [ 24 ], these native species are quite a constant element of the P. velutina association.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little attention has been paid to understanding the impacts of exotic species on indigenous woody plant communities in riparian zones. In this context, one significant invader plant commonly occurring within the riparian areas alongside the Molopo River in the North-West Province and provoking serious economic and ecologic concerns is P. velutina [ 24 , 25 ]. The dominance of P. velutina reduces the physiognomic heterogeneity of riparian habitats.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds are found in the wild and have low commercial value. It is a legume of the bean, pea, caraota, and quinchoncho family, Mimosaceae [20][21][22][23]. The protein of mesquite constitutes 60% of the weight of the seeds, but for animals to benefit from it, the pods and seeds must be crushed; otherwise, they pass through the digestive tract without being digested.…”
Section: Introductionmentioning
confidence: 99%